Enhancement Attempts for a Three-Bladed Savonius Turbine Performance - Mohamed, Mohamed H.; Alqurashi, Faris; Ramadan, A.; Thévenin, D. (Frontiers in Energy Research, 2022)
In this work the performance of a new wind turbine design derived from a conventional Savonius turbine is investigated by numerical simulations. The new design consists of three blades without passage between them (closed center). All unsteady computations (in the next sections mean as well Computational Fluid Dynamics) presented in the current work depend on a commercial software ANSYS-Fluent 19. In particular, the blade geometry, the influence of a deflecting plate and the influence of mobile parts on the returning plate have been investigated in details. Since first results were partly disappointing for the turbine with deflector but it is very interesting for turbine with opening blade, these same properties have been also investigated for the classical Savonius turbine. By comparison between both, an optimal solution can emerge from this first study for these designs. The results indicated that the opening blade design improved the performance by 25.9% at lambda=0.7, however, the deflecting plat reduces the performance along the operating range.